Springs of Life: Spas in Western Galicia from the Beginning of the 19th Century to the Outbreak of World War I - Hojka, Zbigniew (Studia Historiae Oeconomicae, 2024)
Some of the spas there trace their origins to the first half of that century. Thanks to its diverse natural and geographic environment Western Galicia was somehow predestined to establish spas. There were mineral waters and a favorable microclimate. An additional advantage was the mountainous natural environment, especially, in the south of the region, which was mostly pristine. Even though some spas originated in the first part of the century, their dynamic development began to be observed only from the middle of the same century. The number of visitors also began to grow dynamically. The most fashionable place in the middle of the century was Szczawnica. However, it gradually lost this position as a result of increasing competition from other spas and internal problems. Before the outbreak of World War I, Zakopane clearly led the way. The state of the spas depended on the people managing them, mainly, on their commitment. Alongside large spas like Zakopane and Szczawnica existed smaller ones with poorly developed accommodation. They were treated by visitors more as a summer resort than a health resort. The purpose of the article is to show the development of spa treatment in the 19th century and early 20th century. It was based on the sources of medicinal waters discovered in western Galicia. Consequently, these areas became a kind of spa basin, popular among patients. The selected individual spas are discussed, their establishment and development are described, factors influencing the growth of their popularity and obstacles to their development are indicated. Changes in the interaction between man and nature in relation to Western Galicia are shown. It allows to understand the inspiring role of nature in the everyday life of man.